PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER dan RETURN ON ASSET TERHADAP NILAI PERUSAHAAN - Amri Amrulloh; La Ode Abdullah; Amir Ramdan; Mia Laksmiwati (Universitas Budi Luhur, 2022)
This study aims to determine the effect of the current ratio on firm value, the effect of debt to equity ratio on firm value, the effect of total asset turnover on firm value, return on assets on firm value in metal sub-sector companies and the like on the Indonesia Stock Exchange in the 2017-2017 period. 2021. Samples were taken using purposive sampling technique. The population in this study were 17 companies and the sample used was 13 companies. Multiple Linear Regression analysis method with IBM SPSS 23.0 analysis tool. The results showed that the current ratio had no significant effect on firm value, debt to equity ratio had a positive and significant effect on firm value, total asset turnover had no significant effect on firm value, return on assets had a positive and significant effect on firm value.